Repetitive Transcranial Magnetic Stimulation (RTMS) as a Treatment for Post-concussion Syndrome - Rutherford, Grant; Lithgow, Brian; Mansouri, Behzad; Sulieman, Abed; Pouya, Omid Ranjbar; Dastgheib, Zeinab; Zhang, Weijia; Salter, Jennifer; Moussavi, Zahra (CMBES Proceedings, 2017)
As part of an ongoing study, a small group of volunteers with post-concussion syndrome (PCS) were given either real or sham rTMS treatment. Thirteen treatment sessions over three weeks applied 20 Hz rTMS to the left dorsolateral prefrontal cortex. Assessments to determine cognitive ability, memory, depression symptoms, and PCS symptom burden were done before and after treatment, and twice following up at one and two months post-treatment. Significant improvements were found at two months post-treatment in the measurement of symptom burden using the Rivermead Post Concussion Symptoms Questionnaire. This result suggests that rTMS may be an effective treatment for some of the symptoms of post-concussion syndrome.